2016
DOI: 10.1016/j.cedpsych.2016.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Bilingualism and phonological awareness: Re-examining theories of cross-language transfer and structural sensitivity

Abstract: The purpose of this study was to examine the relationship between bilingualism and phonological awareness by re-evaluating structural sensitivity theory and expanding cross-language transfer theory. The study was conducted with three groups of 1st and 2nd graders matched in age, SES and non-verbal IQ: a) monolingual English-speaking children from a general education program, b) native Japanese-speaking children from a Japanese-English two-way immersion bilingual program and c) native English-speaking children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 45 publications
6
28
0
5
Order By: Relevance
“…It is generally acknowledged that for children learning to read in two languages simultaneously, literacy skills acquired in one language can “transfer,” or have a significant effect on their acquisition of the other language (Cummins, 2012; D’angiulli, Siegel, & Serra, 2001; Geva & Wang, 2001). Theories of transfer postulate that transfer is most likely to happen when there are shared features across the bilinguals’ two languages and when these shared features are more salient in one of the languages than in the other (Kuo, Uchikoshi, Kim, & Yang, 2016). In the case of Chinese-English bilingualism, both English and Chinese are languages with low sound-to-print predictability and with relatively large phono- or morpho-syllabic units mapping onto print (relative to Spanish or Italian, which have greater sound-to-print predictability and more fine-grained sound-to-print mappings; Ziegler & Goswami, 2005).…”
Section: Theoretical Dilemmas In Bilingual Reading Acquisitionmentioning
confidence: 99%
“…It is generally acknowledged that for children learning to read in two languages simultaneously, literacy skills acquired in one language can “transfer,” or have a significant effect on their acquisition of the other language (Cummins, 2012; D’angiulli, Siegel, & Serra, 2001; Geva & Wang, 2001). Theories of transfer postulate that transfer is most likely to happen when there are shared features across the bilinguals’ two languages and when these shared features are more salient in one of the languages than in the other (Kuo, Uchikoshi, Kim, & Yang, 2016). In the case of Chinese-English bilingualism, both English and Chinese are languages with low sound-to-print predictability and with relatively large phono- or morpho-syllabic units mapping onto print (relative to Spanish or Italian, which have greater sound-to-print predictability and more fine-grained sound-to-print mappings; Ziegler & Goswami, 2005).…”
Section: Theoretical Dilemmas In Bilingual Reading Acquisitionmentioning
confidence: 99%
“…In this perspective, general conception postulates that PA goes from larger to smaller sound units [26,17]. Furthermore, children are likely to develop their phonological sensitivity as they grow older in an independent manner that capacitates their language abilities to become stable [17,23,25]. A study by Bandini et al [14] on 254 elementary school children aged between 5 to nearly 7 years old aimed to investigate the existing relationships between PA abilities and phonological working memory, presented that children aged 5 to 6 years old portrayed a good mastery of syllabic and onset-rime awareness.…”
Section: What Is Phonological Awareness (Pa)?mentioning
confidence: 99%
“…Reading is known to be the core of academic success and one of the keys to reading success among young learners is the knowledge in phonological awareness (PA). PA has been known for decades to be one of the most crucial precursors of word reading in language learning and is able to predict later reading among young learners [23,13]. PA in Malaysia is still considered new and yet to be uncovered [43].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, more research needs to examine groups of bilinguals who are receiving similar instruction and to target children both in mainstream classrooms in which all instruction is in English and in bilingual classrooms in which English instruction is supplemented with instruction in the home language. In a recent study, we compared bilingual children with different language dominance enrolled in the same classrooms and receiving the same literacy instruction (Kuo, Uchikoshi, Kim, & Yang, ). In this cross‐sectional study, we found that both Japanese–English and English–Japanese bilingual children in dual language first‐ and second‐grade classrooms performed similarly and scored higher than their English monolingual classmates on questions that included, for example, syllables with onsets shared between Japanese and English.…”
Section: Background Literaturementioning
confidence: 99%